Fluorescence properties of retinoid X receptor antagonist NEt-SB. (1st January 2021) - Yamada, Shoya; Takamura, Yuta; Fujihara, Michiko; Kawasaki, Mayu; Ito, Sohei; Nakano, Shogo; Kakuta, Hiroki
Graphical abstract: Abstract: Ligands of retinoid X receptors (RXRs) are effective against various diseases, so there is a need for efficient screening methods to discover new ligands. Existing screening methods are complex and time-consuming, and a simple fluorescence assay would be highly desirable. Here, we focused on NEt-SB (4 ), which has a stilbene structure, as a candidate for this purpose, and examined its fluorescence properties in detail. The fluorescence intensity of 4 was remarkably increased in highly viscous solvents and upon binding to hRXRα-LBD, due to suppression of free rotation of the stilbene moiety. Although the relatively low fluorescence intensity and the short fluorescence wavelength of 4 make this compound itself unsuitable for use in RXR binding assay, our findings provide a basis for further structural evolution, which may lead to a derivative that would be suitable for fluorescence assay of RXR binders.